Feasibility and efficacy using the KODEX-EPD imaging system in right atrial flutter ablation: a single center experience. (14th October 2021) - Schillaci, V; Stabile, G; Shopova, G; Arestia, A; Agresta, A; Salito, A; Solimene, F
Abstract: Background: Isthmus-dependent right atrial flutter is the most frequently encountered atrial flutter in clinical practice (80–90% of atrial flutters). Purpose: The aim of our study was to assess as first experience the feasibility and safety of radiofrequency catheter ablation (RFCA) of cavo-tricuspid isthmus (CTI) guided by KODEX-EPD imaging system in patients presenting with typical atrial flutter (AFL). Methods: 16 consecutive patients (mean age 68, 46±7, 8 years, 80% males) with diagnosis of AFL underwent RFCA guided by KODEX-EPD imaging system. In 15 patients the analysis performed during tachycardia showed a counter-clockwise activation. In 1 patient no tachycardia could be induced and the ablation was performed in sinus rhythm with fixed pacing from the coronary sinus. The KODEX-EPD imaging system was also used to guide ablation and to confirm persistent bidirectional block after ablation. Results: Mean procedural time was 37, 6±8, 2 min, mean radiofrequency ablation time was 7, 8±3, 4 min, and mean fluoroscopy time was 2, 1±1, 2 min. All procedures were acutely successful with interruption of AFL during RFCA along the inferior CTI in 15 patients and achievement of the bidirectional conduction block in 16 patients proven by atrial pacing medial and lateral to the ablation line. There were no major procedural and 30-day complications. Over a mean follow-up of 18 months, we observed no recurrence of arrhythmia and no complications. Conclusions: Our study shows that RFCA for AFL using the KODEX-EPD imaging system is feasible, safe, and effective. Funding Acknowledgement: Type of funding sources: None.